2007
DOI: 10.2486/indhealth.45.552
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nap Length, Nap Timing and Sleep Quality on Sustaining Early Morning Performance

Abstract: The study examined how nap length, nap timing and sleep quality affect early morning performance (6:00 to 8:00). Twelve students participated in a simulated nightshift schedule (22:00 to 8:00) where the length and timing of nocturnal naps were manipulated (0:00-1:00, 0:00-2:00, 4:00-5:00 and 4:00-6:00). A performance test battery was administered consisting of a psychomotor vigilance test, a logical reasoning test, and a visual analogue scale for subjective fatigue and sleepiness. The results showed that a 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
(57 reference statements)
1
24
0
Order By: Relevance
“…Several studies have shown that naps increase performance on objective measures of sleepiness such as vigilance and time reaction tests (114)(115)(116)(117). Studies on the effects of naps during night work have also shown improvement on measures of subjective sleepiness (114,116,(118)(119)(120).…”
Section: Napsmentioning
confidence: 98%
“…Several studies have shown that naps increase performance on objective measures of sleepiness such as vigilance and time reaction tests (114)(115)(116)(117). Studies on the effects of naps during night work have also shown improvement on measures of subjective sleepiness (114,116,(118)(119)(120).…”
Section: Napsmentioning
confidence: 98%
“…Night-shift work can cause not only occupational accidents due to severe sleepiness but also can introduce several health problems (Folkard and Tucker 2003). Taking a nap is one of the eVective countermeasures to prevent increasing sleepiness and decreasing alertness during sleep deprivation (Kubo et al 2007). Previous research related to nightshifts has examined various kinds of napping strategies to counteract the problem among night shift workers; one such strategy is taking a prophylactic nap before the night of sleep deprivation.…”
Section: Introductionmentioning
confidence: 99%
“…Work performance has been used as a behavioural index of fatigue 21,39) , and cumulative workload induced fatigue was expressed as a transient decrease in work performance. However, it should be borne in mind that work performance is affected by a number of factors, such as sustained attention, circadian rhythms and extrinsic and intrinsic motivation 7,40,41) . Therefore, interactions among these factors make it difficult to interpret data on work performance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identification of effective measures to counteract the fatigue and sleepiness associated with night work has become an important focus of investigation in the field of occupational health. The effectiveness of naps 7,8) , caffeine 9) , ventilation 10) , bright light 11) and music 12) as measures to combat the adverse effects of night work has been examined in previous studies.…”
Section: Introductionmentioning
confidence: 99%